THE INTERSECTION OF GOVERNMENT SPENDING AND FINANCING MECHANISMS: PERSPECTIVES FROM GHANA - Ampomah, Kwame Ato (International Journal of Current Practice in Management and Leadership (IJCPML), 2024)
Government expenditure is a pivotal driver of economic growth globally, facilitating infrastructure development and institutional support. However, the financing channels for these expenditures play a crucial role in shaping economic trajectories. This paper delves into the intricate relationship between government expenditure and its financing modes. While conventional wisdom dictates that government spending should primarily rely on direct and indirect taxes, as well as non-tax revenues, many developing nations resort to borrowing to bridge budgetary shortfalls. This paper explores the dynamics of these financing methods and their mutual influences. It sheds light on the challenges faced by governments in balancing their budgets and underscores the imperative of sustainable fiscal policies.